ANALISIS KESTABILAN LERENG PENAMBANGAN NIKEL PADA PT. GAG NIKEL DENGAN MENGGUNAKAN METODE BISHOP - Papua Dorus Rumsowek; Indra Birawaputra (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
It is important to understand the condition of the slopes formed and the FK values obtained from the results of slope analysis in order to provide a safe FK value based on standard requirements for nickel mining slopes. The problems found in the study are, what variables are used in calculating FK values as well as the presence of safe FK values and level geometries that are ideal for mining activities. Thus, the results of one of the main variables used to calculate the slope balance are Bishop method, and get FK values from one different methods, namely 1.144 by looking at the characteristics of the soil and rocks.